Corporate Social Responsibility (CSR) Perspektif Hadis: Implementasi Nilai Islam dalam Ekonomi Modern - Muhammad Sauqi; Alya Rohani; Mar’atun Solehah (Al Rikaz: Jurnal Ekonomi Syariah, 2025)
Corporate Social Responsibility (CSR) in Islamic economics is a concept that emphasizes the importance of achieving a balance between the profits earned by a company and the positive impact it provides to society through various social and economic programs. In the context of Islamic entrepreneurship, CSR strives to balance company profits while simultaneously benefiting society through various social and economic initiatives. The ethical principles of Islamic business that underlie CSR include justice, mutual assistance, and environmental sustainability. In Islam's view, CSR is not just about fulfilling legal and moral obligations but also a strategy to ensure the continuity of the company and the long-term welfare of society. Islamic economic actors have the duty to assist the community and preserve the surrounding environment. The implementation of CSR from an Islamic perspective must align with maslahah, which includes both dharuriyyah (basic needs) and hajiyyah (secondary needs). Some of the Islamic business principles related to CSR include environmental protection, efforts to alleviate poverty, and prioritizing urgent needs. CSR in Islamic business is a moral responsibility of business actors as representatives of the company to Allah SWT, with the aim of obtaining both worldly and spiritual benefits, making every action in business an act of worship.